STRATEGI KONSELOR DALAM MENINGKATKAN MOTIVASI KERJA PEGAWAI DI RUTAN KELAS II B SIDENRENG RAPPANG (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2023)
The main research problem is "What is the counselor's strategy in providing work motivation guidance to class IIB Sidrap detention center employees?" What are the inhibiting and supporting factors of the motivational guidance strategy carried out by counselors against Class IIB Sidrap detention center employees? This study uses a descriptive qualitative research type which is located in the Class II B Detention Center in Sidenreng Rappang. The research approach used is the guidance approach and counseling approach. The primary data source for this writing is that in this study the key informants were Iskandar DJ, AMd, Ip, SH as the head of the Sidrap Class II B Detention Center, and an additional informant, namely Yabu. S. Sos As Head of Sidrap Class IIB Detention Center Sub-Management, as well as Class IIB Sidrap Detention Center Staff. With a total of 45 employees plus 8 Civil Servant Candidates, the number of employees assigned to the Internal Compliance Operational Unit is 5 people. Secondary data sources include books, theses, journals, literature, and other data that can be used as a complement. Data collection methods are observation, interviews, and documentation. Data analysis was carried out in three stages, namely data reduction, data presentation, and concluding. The results of this study indicate that there are two steps used by counselors in providing work motivation guidance to employees of Class II Sidrap Detention Center, namely: Taking a personal approach or individual counseling approach to employees of Class II B Detention Center in Sidrap and open discussion with employees and counselor. Obstacles in providing work motivation to employees of the Sidrap Class II B Detention Center are employees who find it difficult to accept suggestions or seem stubborn, as well as the selfish nature of employees.